Location Analysis of Interest in Buying Housing in South Tangerang City - Nursoleh, Nursoleh (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
South Tangerang is an urban city, so its population growth is always increasing. Therefore, various forms of property business have emerged, ranging from housing types to clusters. For property business actors, this is an opportunity that must be taken, but it is necessary to consider aspects of purchasing decisions. This study aims to analyze the location factor, its relation to home buying decisions in the city of South Tangerang. The research method uses quantitative, and the data is obtained through the distribution of questionnaires. The research sample amounted to 100 people with saturated sampling technique. The results of the study stated that the majority of consumers would buy a house with a strategic location. Namely, the location of the house that is close to work access, public facilities, and government. The contribution value of 33% means that the average consumer in the city of South Tangerang places location as a third of purchasing decisions. That is, whether or not to buy a house, there is a third determined by the location factor.